2016
DOI: 10.14393/bj-v32n6a2016-32741
|View full text |Cite
|
Sign up to set email alerts
|

Selection and characterization of Bacillus thuringiensis isolates with a high insecticidal activity against Spodoptera frugiperda (Lepidoptera: Noctuidae)

Abstract: Spodoptera frugiperda (SMITH, 1797) (Lepidoptera: Noctuidae) affects diverse crops of great economic interest, for instance, it can cause severe yield losses in maize, rice and sorghum. In this study, a selection and characterization of Bacillus thuringiensis (BERLINER, 1911) isolates with a high insecticidal activity against S. frugiperda was performed. Fifty-two crystal-forming B. thuringiensis isolates that were identified from 3384 Bacillus-like colonies were examined and screened by PCR for the presence c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…These greenhouses are used to grow plants from the equatorial climate. The ratio of B. thuringiensis isolates comparing to all grown isolates noted in this work (~ 4%) was comparable to other reports, describing B. thuringiensis isolations from different geographic locations and various samples, where this value reached 1.5-5.0% (Berón and Salerno 2006;Ramalakshmi and Udayasuriyan 2010;Aramideh et al 2016;Cerqueira et al 2016;Lone et al 2017), but it was lower than in some other studies, showing that B. thuringiensis accounted for 10-60% of the isolates (Kim 2000;Apaydin et al 2005;Rabha et al 2017). Noteworthy is the fact that despite evident activity of BG11/BG12/BG15 strains against lepidopterans (they harbour genes encoding lepidopteran-active Cry1Ba/1Ia/2Ab/9Ea and Vip3Aa insecticidal proteins and were proven to be active against C. pomonella and S. exigua larvae), insects representing Lepidoptera order are not noted in the tropical greenhouses No.…”
Section: Discussionsupporting
confidence: 91%
“…These greenhouses are used to grow plants from the equatorial climate. The ratio of B. thuringiensis isolates comparing to all grown isolates noted in this work (~ 4%) was comparable to other reports, describing B. thuringiensis isolations from different geographic locations and various samples, where this value reached 1.5-5.0% (Berón and Salerno 2006;Ramalakshmi and Udayasuriyan 2010;Aramideh et al 2016;Cerqueira et al 2016;Lone et al 2017), but it was lower than in some other studies, showing that B. thuringiensis accounted for 10-60% of the isolates (Kim 2000;Apaydin et al 2005;Rabha et al 2017). Noteworthy is the fact that despite evident activity of BG11/BG12/BG15 strains against lepidopterans (they harbour genes encoding lepidopteran-active Cry1Ba/1Ia/2Ab/9Ea and Vip3Aa insecticidal proteins and were proven to be active against C. pomonella and S. exigua larvae), insects representing Lepidoptera order are not noted in the tropical greenhouses No.…”
Section: Discussionsupporting
confidence: 91%
“…Cry 1Ac represented 45.9% of 17 strains observed by Cerqueira et al. (2016), and Şahin et al. (2018) identified cry 1Ac in five isolates out of 80 strains.…”
Section: Discussionmentioning
confidence: 89%
“…The frequency of cry1Ac found in the present study is similar to the results observed byKaviyapriya et al (2019), who identified the presence of cry1Ac in strains producing high mortality levels on invasive lepidopterans pests. Cry1Ac represented 45.9% of 17 strains observed byCerqueira et al (2016), andŞahin et al (2018) identified cry1Ac in five isolates out of 80 strains.…”
mentioning
confidence: 97%